Analysis Of Gen Z Entrepreneurs' Interest Towards Halal Certification - Haryanti, Peni (Jurnal Ilmiah Ekonomi Islam, 2024)
This study aims to assess the level of literacy among Gen Z entrepreneurs in the food sector regarding the importance of halal certification and examine its influence on their attitudes and interest in obtaining it. The research method applied is quantitative. Primary data was collected through the distribution of questionnaires to Gen Z entrepreneurs. The targeted outcome of this research is to provide a deeper understanding of the relationship between halal certification literacy, attitudes, and the interest of Gen Z entrepreneurs in acquiring the certification. The findings are expected to measure the literacy level of Gen Z entrepreneurs in the food sector on the importance of halal certification and assess its impact on their attitudes and interest in obtaining it.